A hybrid approach for the machinability analysis of Incoloy 825 using the entropy-MOORA method - Sahu, Saurabh Kumar; Shekhar, Shiena; Khan, Akhtar; Soni, Dheeraj Lal; Gangwar, Prashant Kumar; Gupta, Manish (High temperature materials and processes, 2024)
With its exceptional qualities, Incoloy 825 is highly valued in a range of industries, including nuclear power plants, petrochemical plants, and chemical industries. Nevertheless, the unique combination of these properties presents a formidable challenge when it comes to machining Incoloy 825. Its low heat conductivity, rapid strain hardening, strong chemical affinity, and the presence of hard and abrasive particles in its microstructure all contribute to the difficulty. The objective of this study is to examine important factors related to the machinability of Incoloy 825. To achieve this, a hybrid tool called entropy coupled with MOORA will be used to determine the optimal cutting conditions. In order to achieve this, three specific input parameters were chosen: the spindle speed, feed rate, and depth of cut. Meanwhile, the major outcomes taken into account were the cutting force, cutting temperature, material removal rate, roughness of the machined surface, and flank wear. The experiments were conducted using Taguchi’s L orthogonal array, following the principles of experimental design. The findings indicate that the proposed hybrid approach is capable of accurately determining the best combination of parameters for cutting the chosen work material and can be employed in structural applications. For turning Incoloy 825, the optimal parametric setting was determined to be a spindle speed of 1,285 rpm, a feed rate of 0.0625 mm·rev , and a depth of cut of 0.3 mm.